Comparison of the Effectiveness of Emotion-Focused Therapy Group and Schema Group Therapy on the Difficulties in Emotion Regulation and Health Promoting Lifestyle of Obese Women - Yaghoubi 1, Reza; Bayazi 2*, Mohammad Hossein; Babaei 3, Mahnaz; Asadi 1, Javanshir (Shahroud Journal of Medical Sciences, 2020)
Background: Obesity is one of the most common problem among women, leading to many chronic diseases such as heart disease and cancer. Various factors such as emotional problems and lifestyle have a special role in women's obesity. The aim of the present study was to compare the effectiveness of emotion-focused therapy group (EFT-G) and schema group therapy (SGT) on the difficulties in emotion regulation and the health-promoting lifestyle of obese women referred to nutrition clinics in Mashhad in 2018.Methods: Thirty-six obese volunteer women were selected and assigned into two experimental groups (each group consisted of 12 women) and a control group (n = 12). A meeting was held to explain the objectives of the research and intervention. Each one of the experimental groups received 90-minute weekly sessions for 2.5 months (10 sessions), while the control group did not receive any intervention. Before and after the training phase, all of the participants completed the demographic questionnaire. Finally, they had also completed the difficulties in emotion regulation scale and the health-promoting lifestyle profile. Data were analyzed by using SPSS 22 software. The significant level was set at 0.05.Results: The outcomes of data analysis by using multivariate analysis of variance (MANOVA) indicated that there is no significant difference between the two experimental groups on the research variables (Pvalue>0.05). The results also showed that EFT-G and SGT improved health promoting lifestyles and difficulties in emotion regulation in obese women (Pvalue<0.05). Also, the results showed that EFT-G was effective on difficulties in emotion regulation, but group schema therapy was not effective on emotional regulation difficulties in obese women (Pvalue>0.05).Conclusions: Generally, the results showed that there is no significant difference between the two experimental groups on the difficulties in emotion regulation and health-promoting lifestyle. The EFT-G decrease the difficulties in emotion regulation and increase the health promotion lifestyle in obese women. Furthermore, this study illustrated that the EFT-G can improve the difficulties in emotion regulation and the health promotion lifestyle of obese women.Keywords: Emotion-focused therapy, schema group therapy, Obesity, Difficulties in emotion regulation, Health promotion lifestyle